Semantic Analysis and Network Expansion for Enhancing Thai and Lao Ontologies - Meemongkol, Gornkrit (Journal of Arts and Thai Studies, 2024)
Objectives: A key challenge in developing computational language processing systems lies in systematically explaining the process by which the human brain links the meanings of words. This remains a complex and elusive issue that defies comprehensive explanation. To study and analyze the human’s cognitive processes involved in meaning association and the creation of semantic networks, this research aimed to lay the groundwork for applying such knowledge to enhance the efficiency of computational language processing systems in the future. This research specifically seeked to analyze the expansion of semantic networks for the development of ontologies in the Thai and Lao languages. Methods: This study initiated by selecting Thai words based on specific criteria and extracting their definitions from dictionaries. These definitions were then analysed to find the relationship between words and contexts by comparing with those findings of the study in Phase 1. Concurrently, corresponding Lao words were explored to understand their meanings, which were validated through comparison with their Thai counterparts. Finally, an expansion of meanings within the semantic network was proposed, considering both words and contexts. Results: The findings identified significant expansions within the semantic network. For instance, 1. "window" extended its meaning to include "hole," 2. "mirror" encompassed "(camera) lens " and "transparent plastic," 3. "watch repair shop" was associated with "dead," "non-operational," and "damaged," 4. terms like "stranger," "representative," and "unfamiliar person" were expanded to include "representatives," "appointment," "trust," and "unknown person," 5. the semantic network of "police station" was broadened to include "uniform," "weapons," and "arresting," 6. "detergent" included "laundry service" and "housekeeping," 7. other expansions included "New Year’s Day" with "new beginning," "celebration," and "festival," 8. "certificate" with "school" and "organizations authorized to issue certificates," 9. "ticket booth" with "buying and selling services," and 10. "calculator" with "calculate," "mobility," and "use of electricity or solar energy.". Application of this study: The findings of this study can contribute to the development of Thai and Lao language ontologies, enhance knowledge and understanding of semantics, and broaden the scope of linguistic knowledge, thereby fostering its wider application and dissemination.